Information constraints and the precision of adaptation: Sex ratio manipulation in wasps - Shuker, David M. (National Academy of Sciences, 2004)
Sex allocation theory offers excellent opportunities for studying the precision of adaptation. One of the best-supported areas in the field of sex allocation is Hamilton's theory of local mate competition, which predicts female-biased offspring sex ratios when populations are structured such that mating takes place locally before females disperse. As predicted by local mate competition theory, females of numerous species, especially parasitoid wasps, have been shown to lay a less female-biased sex ratio as the number of females simultaneously laying eggs on a patch increases. It has usually been assumed that this sex ratio adjustment comes through individuals adjusting their behavior directly in response to the presence of other females. Here we show that in the parasitoid wasp Nasonia vitripennis, this shift in offspring sex ratios is primarily caused by the presence of eggs laid by other females and to a lesser extent by the presence of other females. We confirm that females are behaving as predicted by theory, but the way in which they do so is not as straightforward as is often assumed. Instead, even when there are multiple females on a patch, individuals still use the cues that are more commonly associated with sex ratio adjustment in response to sequential visits to a patch by females. This result provides a possible explanation for the observed variation in N. vitripennis sex ratios. More generally, it confirms the need to consider the mechanistic basis of a behavior to understand fully its adaptive value.